GIANT LEIOMYOSARCOMA WITHOUT SYMPTOMS - Belceska, Gordana; Bundovska, Smiljana (Journal of Morphological Sciences, 2020)
Of all types of sarcomas, about 25% are leiomyosarcomas. We report a case of a young woman aged 35 years with asymptomatic leiomiosarcoma, who came for an examination due to hypochromic anemia. Due to the patient's age and the asymptomatic course of the disease, this case is specific and differs from previously published cases of giant LMS.                                   Key words : leiomiosarcoma, giant, asimptomatic